The Role Of Color In The Attainment Of Customers’ Intensive Buying Intention: An Exploratory Descriptive Case Study (S.O.R Model Application) - AYAD, Dr. Saleh; BENHABIB, Pr. Abdrezak (Recherches économiques et managériales, 2016)
This research work studied the influence of colors in groceries, as an atmospheric variable, on the customer’s impulsive intention of buying. In the literature review, the researcher introduced the theoretical and methodological bases responding to this problematic situation. An experiment was made in the laboratory where 200 participants had visited a virtual grocery with 4 different color conditions (red, yellow, blue and green). Then they answered a questionnaire about the variables of this study. The results showed that colors influence the customer’s impulsive intention of buying either directly or through affect as intermediary.   Key words: the color, the impulsive intention of buying, affect الملخص:   الهدف من هذه المقالة هو دراسة تأثير اللون كمتغير بيئي لمتاجر المواد الغذائية على إثارة نية الشراء الاندفاعي عند المستهلكين، مع الاستناد إلى الشعور كوسيط. من اجل معالجة هذه الإشكالية استندنا على مسح أدبي منهجي في دراسة المتغيرات محل الدراسة. أنجزنا تجربة داخل المخبر على 200 مختبر يزورون افتراضيا متجر للمواد الغذائية بأربعة شروط لونية مختلفة (الأحمر، الأصفر، الأزرق، الأخضر)، ثم يجيبون على أسئلة تتعلق بإشكالية البحث. النتائج أظهرت تأثيراللون في بروز نية الشراء الاندفاعي بطريقة مباشرة، أو غير مباشرة عن طريق الشعور كوسيط.  الكلمات المفتاحية: اللون، نية الشراء الاندفاعي، الشعور.        I.            Introduction: